Human Rights As An Embodiment Of Social Justice - Kemi Anthony Emina (Journal of Public Administration and Government, 2021)
The violation of human rights is a serious threat to society which is constituted for the sake of human beings. Individuals and society are inseparable from each other. Society provides opportunities for individual growth provided he/she utilizes it appropriately and delivers the duties towards the fulfillment of the social goal. Being a part of society he/she has the privileges to enjoy all the basic rights and freedom. It is the rights that protect individual liberty from external aggression. This work discusses the concept of human rights as an embodiment of social justice. It starts by discussing the concept of human rights, the notion of Rights from Indian philosophical tradition. This work also compares the Kantian concept of Rights with John Rawls. These works conclude that the Rawlsian difference principle has similarities with the Indian reservation system, which is formulated by the Indian Parliament for the betterment/welfare of minorities groups. During ancient times, sudras being born in a lower class were treated as slaves and are deprived of minimum social justice. Only Brahmans are considered to be pure who are free to take part in every religious activity.